Oliver Mtukudzi Living Tuku Music in Zimbabwe. Jennifer W. Kyker. 2016. Bloomington and Indianapolis: Indiana University Press. 25 images, 3 transcriptions, bibliography, index, 290 pp. - Thram, Diane (International Library of African Music, 2017)
pages: 173-175
Keywords: African Music; Zimbabwe; Tuku Music